Empowering Teenagers Through Gender-Segregation Education: A Case Study On School Management - Finadatul Wahidah; Dewi Sinta (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
The goal of this research is to examine the effects of single-sex education management on the empowerment of teenagers, focusing on both academic and non-academic outcomes. Research approach using qualitative case study type. Data collection in this study will be carried out using three primary methods: observation, interviews, and documentation. Data analysis uses Miles and Huberman. The Finding of this research shows that gender-segregation education or single-sex schools management make students feel freer to explore their interests and talents without the social pressure of gender stereotypes. Students focus more on education without the distractions of gender biases often present in co-educational settings. The novelty of this research lies to update perspectives on single-sex education management and how it can contribute to character development and academic achievement. The theory of gender differences in educational management contexts is also enriched by these findings, challenging traditional assumptions that co-education is more effective. Class management with two sections of men and women, a curriculum development system, and the division of tasks for administrators are managed effectively and efficiently by the head. The study provides new insights into the different learning experiences of male and female students and opens the door to developing more gender-specific teaching methods.Keywords: Education, Gender-Segregation, School Management,Teenagers